2006
DOI: 10.1177/154405910608500115
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors of Early Childhood Caries in a Southeast Asian Population

Abstract: A retrospective cohort study on ECC and associated factors was conducted among mothers with 25- to 30-month-old infants in a community where prolonged breastfeeding was common practice. All infants who consumed sugary supplementary food or rice that was pre-chewed by the mother, or who fell asleep with the breast nipple in their mouths, had ECC. Infants without those habits, and who were breastfed up to 12 months, had no ECC. Breastfeeding during the day beyond the age of 12 months was not associated with ECC,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
90
3
13

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(118 citation statements)
references
References 8 publications
5
90
3
13
Order By: Relevance
“…Yet in another study, the children were weaned from the bottle during the day, but continued nighttime bottle feeding (Riedy et al, 2001). Another Asian study showed an increased risk for ECC due to prolonged duration of breast-feeding (van Palenstein Helderman et al, 2006). In some studies, mothers indicated that other caregivers encourage use of the bottle/sugar in diet when the mothers were away at work, even though mothers were not in favor of such practices (Amin & Harrison, 2009;Riedy et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Yet in another study, the children were weaned from the bottle during the day, but continued nighttime bottle feeding (Riedy et al, 2001). Another Asian study showed an increased risk for ECC due to prolonged duration of breast-feeding (van Palenstein Helderman et al, 2006). In some studies, mothers indicated that other caregivers encourage use of the bottle/sugar in diet when the mothers were away at work, even though mothers were not in favor of such practices (Amin & Harrison, 2009;Riedy et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…A similar practice of mothers feeding their children rice that was pre-chewed by them for 20 seconds has been reported in a previous study and is probably a cultural practice of the south-east Asian region. In the above mentioned Myanmar community, ECC was considered inevitable and parents were not aware of the etiology (van Palenstein Helderman et al, 2006). Hence culturally appropriate and targeted strategies aimed at these modifiable practices need to be wisely promoted so that the oral health burden carried by these children can be reduced (Amin & Harrison, 2009;Schluter et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…This shows that more than half of the study population does not have knowledge about the effects of feeding before sleep. A previous study showed an increased risk for ECC with a prolonged duration of breastfeeding [18]. In another study, urban Mexican American and immigrant Latino mothers express uncertainty as to how bottle-feeding was detrimental to oral health [19,20].…”
Section: Discussionmentioning
confidence: 99%
“…6,63 Geceleri tükürük üretiminin ve akış hızının azalması, ağız temizliğinin yapılamamasına bağlı olarak çocuklara 1 yaşından sonra uzun süreli ve gece beslenme yapılması EÇÇ için yüksek risk oluştur-maktadır. [64][65][66] Meyve suları ve meşrubatlar, düşük pH (pH 3-4)'ye sahiptir ve yüksek miktarda sükroz içerdiğin-den eroziv ve karyojenik etkileri vardır. Bu içeceklerin fazlaca tüketilmesi, genellikle çocuk her istediğinde ve tercihen biberonla verilmesi, tü-kürüğün yetersiz remineralizasyon aktivitesi ile birleşince EÇÇ'de ortak bulgu olan mine de demineralizasyon sürecinin başlamasıyla sonuçlanmak-tadır.…”
Section: Eçç'ni̇n öNlenmesi̇nde Korunma Strateji̇leri̇unclassified